(3GdJehjd hGOQGI GdeDSSGJ GdeGdjI (B/s - (3GMeO, jhSa YHO GdhgGHs ((3YeGf (B: s (3OGQ GdMGeO(B, s, 2008)
(3jMJhj GdcJGH Ydi (B: (3eaghe GdJehjd hGdEOGQI GdeGdjI , GdbQGQGJ GdESJKeGQjI hJbhje eTQhYGJ GdESJKeGQ , bQGQGJ GdJehjd hgjcd QCS GdeGd hJMdjd GdbhGFe GdeGdjI , UjZ GdJehjd GdESdGejI ,JYQja GdfbhO hhXGFagG h GgejJgG, GdEFJeGf h OhQ GdeSDhdjGJ GdeGdjI aj GdJfejI GdEbJUGOjI , GdHfhc hGdeUGQa , EOGQI QCS GdeGd , TQcGJ GdJCejf , GdeQGLYs
(3HjHdjhZQGajG U(B.207s
Keywords: (3GdGOGQI GdeGdjIs; (3GdJehjds; (3eDSSGJ eGdjIs